Analisis Faktor – Faktor yang berhubungan dengan Kepatuhan Diet pada Pasien Diabetes Melitus: Analysis of Factors Associated with Dietary Adherence Among Patients with Diabetes Mellitus - Zahrotul Jannah; Teti Oktianingsih; Saka Adhijaya Pendit (LPPM STIKES Guna Bangsa Yogyakarta, 2026)
Background Diabetes mellitus is a chronic metabolic disease that requires long-term management, particularly adherence to dietary recommendations, to achieve optimal glycemic control and prevent complications. According to the latest World Health Organization (WHO) report in 2023, the global number of people living with diabetes mellitus continues to increase and is estimated to reach approximately 422 million. Dietary adherence plays a crucial role in improving quality of life and reducing the risk of both acute and chronic complications. However, many patients still experience difficulties in consistently following dietary recommendations. Objective: This study aimed to determine the factors associated with dietary adherence among patients with diabetes mellitus, with particular emphasis on family support, knowledge, and attitudes. Methods: This study employed a quantitative cross-sectional design. A total of 99 patients with diabetes mellitus were recruited using purposive sampling based on predetermined inclusion criteria. Data were collected using a structured questionnaire that had been tested for validity and reliability. Data analysis included univariate analysis to describe respondents' characteristics and bivariate analysis using the Chi-square test to examine the associations between variables. Results: The results demonstrated statistically significant associations between family support and dietary adherence (p < 0.05), knowledge and dietary adherence (p < 0.05), and attitudes and dietary adherence (p < 0.05). Patients who received good family support, possessed adequate knowledge, and had positive attitudes were more likely to adhere to dietary recommendations. Conclusion: Family support, knowledge, and attitudes were significantly associated with dietary adherence among patients with diabetes mellitus.